Pretreatment Behaviors and Improved Corrosion Resistance for Cu/Co-Ni-Cu Coating Electrodeposition on Magnesium Alloy. Issue 9 (1st January 2016) - Chai, Ze; Jiang, Chuanhai; Zhu, Kaiyuan; Zhao, Yuantao; Wang, Chengxi; Cai, Fei; Chen, Ming; Wang, Lianbo
Abstract : Pretreatment behaviors of magnesium alloy were investigated systematically using open circuit potential (OCP)/time, change in weight ( ΔW )/time, grazing incident X-ray diffraction (GIXRD) and surface morphology analysis. Residual products formed during pretreatment processes identified by GIXRD were MgHPO4 ·3H2 O for acid pickling, MgF2-x (OH)x and AlF3-x (OH)x for activation and Zn for zinc immersion, respectively. On this basis, Cu layer and Co-Ni-Cu coating (represented as Cu/Co-Ni-Cu coating) were deposited successively on pretreated magnesium alloy. Thickness of the Cu layer deposited on β-Mg17 Al12 was non-uniform, but the Co-Ni-Cu coating deposited on both α-Mg and β-Mg17 Al12 exhibited an extremely uniform thickness. Using Tafel extrapolation of potentiodynamic polarization curves estimated corrosion rates of magnesium alloy before and after deposition. Magnesium alloy undergoing suitable pretreatments coated with Cu/Co-Ni-Cu coating possessed an improved corrosion resistance.